Enhancing tolerance to heat stress, resistance to infectious Bursal Disease and expression of heat shock protein 70 in broiler chickens by early age feed restriction. - Universiti Putra Malaysia, Research Management Centre (Research Management Centre, Universiti Putra Malaysia, 2003)
The hot and humid tropical climate has a highly detrimental effect on growth. feed efficiency, survivability and disease resistance In broiler chickens. Commercial broilers are particularly susceptible to heat stress because metabolic heat production increases with growth rate while heat dissipation does not. We examined the possibilities of modifying the birds' own natural coping mechanisms through early age stimulation. Two experiments was carried out to investigate the effects of stress attributed to early age fasting on heat tolerance and disease resistance in broiler chickens at market age, and to ascertain the mechanisms involved on a molecular level